2000
DOI: 10.1002/1522-2675(20000906)83:9<2231::aid-hlca2231>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von Sulfolenobilinen und deren Cyclisierung zu Chlorinatozink-Fulleren-Dyaden

Abstract: Prof. Dr. Albert Eschenmoser zu seinem 75. Geburtstag gewidmet Synthesis of Sulfolenobilins and Their Cyclization Directed to Chlorinatozinc-Fullerene DyadsA novel chlorinatozinc-fullerene dyad 18 was synthesized to model the photosynthetic reaction center. The synthetic key step for the formation of the dyad 18 is an unusual one-pot reaction of the (sulfolenobilinato)-nickel rac-16a,b with concomitant generation of the chlorin macrocycle and linkage to the [5,6]fullerene-C 60 -I h . This one-pot reaction is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Former investigations demonstrated that pyrroles can be attached with an aldehyde function to nickel tripyrrin intermediate 5 and that carboxylate groups in the opposite α‐position allow cyclization of the initially formed bilins to chlorins (Scheme ). [6a]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Former investigations demonstrated that pyrroles can be attached with an aldehyde function to nickel tripyrrin intermediate 5 and that carboxylate groups in the opposite α‐position allow cyclization of the initially formed bilins to chlorins (Scheme ). [6a]…”
Section: Resultsmentioning
confidence: 99%
“…But then formylations of cyano‐substituted pyrroles fail due to the strong electron withdrawing effect of the cyano function . [6a],…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dyads have shown promising results in molecular device applications for efficient conversion of light to electrostatic energy, , and they are considered good model systems of natural photosynthesis. ,, However, the natural photosynthesis utilizes chlorophylls in the reaction center, where the primary charge separation takes place, and as antenna molecules . As these harvest light with higher efficiency relative to fully conjugated porphyrins, it is quite surprising that relatively few DA dyads have been synthesized where a chlorophyll-like donor, instead of porphyrin, has been linked with fullerene. The photochemical properties of some chlorin−fullerene dyads have been recently characterized. ,, Chlorin−fullerene systems can undergo photoinduced ET in solutions 15,16,20,21 and in solid state. ,, …”
Section: Introductionmentioning
confidence: 99%
“…In particular, the combination with [60]fullerene, has led to very interesting materials [1][2][3][4][5][6][7][8]. It comes as no surprise that chlorins were utilized extensively in electron-tranfer studies because such compounds can be regarded as model compounds for the photosynthetic reaction center with a naturally occuring electron-donor [9][10][11][12][13][14][15][16][17][18]. In all of these contributions, the chlorin was either attached via an azomethine ylide addition [9][10][11] or by a Diels-Alder reaction approach [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%